THE INFLUENCE OF CUSTOMER SATISFACTION, BRAND IMAGE, AND SOCIAL MEDIA MARKETING ON REPURCHASE INTENTION(A STUDY OF SOMETHINC COSMETIC PRODUCT CONSUMERS IN DENPASAR CITY) - Aulia Goldy Siregar; Ni Made Rastini (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The high level of mobility in Denpasar City encourages people to maintain an attractive appearance. Cosmetics serve as a means to enhance personal appearance, thereby intensifying business competition among cosmetic companies in attracting consumers. Somethinc is one of the local brands that has successfully entered Indonesia’s Top 10 beauty brands; however, over the past three years, it has not yet reached the Top 3. Based on a preliminary survey of 40 respondents, most participants indicated a lack of repurchase intention toward Somethinc cosmetic products. This study aims to examine repurchase intention as influenced by customer satisfaction, brand image, and social media marketing. A total of 170 respondents were selected using non-probability sampling with a purposive sampling technique. Data were collected through online and offline questionnaires distributed to residents of Denpasar City. The data analysis techniques employed included descriptive and inferential analysis, comprising multiple linear regression, classical assumption tests, F-test, t-test, and coefficient of determination. The results indicate that customer satisfaction and social media marketing have a positive and significant effect on repurchase intention, while brand image shows a positive but insignificant effect. These findings suggest that customer satisfaction, brand image, and social media marketing collectively contribute positively to enhancing repurchase intention for Somethinc products.